Consumer Sentiment after the Global Financial Crisis. (September 2016) - Lozza, Edoardo; Bonanomi, Andrea; Castiglioni, Cinzia; Bosio, A. Claudio
The present study seeks to analyse the predictive capacity of the Index of Consumer Sentiment (ICS) (a leading index in international market research) in Italy, before and after the global financial crisis. The analysis focuses on the period 2005–2013 and investigates the predictive power of the ICS with regard to two different outcomes: (1) the actual level of household consumption (considering both its absolute value as total spending and its quarterly variations) and (2) consumers' strategies (i.e. reducing their consumption, focusing on discounts and promotions, focusing on quality), both in general and in specific sectors (e.g. food, leisure, health). The study is based on a second-level analysis of data collected by the Italian Statistical Institute (ISTAT) and a tracking survey on Italian consumers' perceptions and strategic intentions (four waves per year, each consisting of 1, 000 telephone interviews based on a structured questionnaire). The findings show that the ICS is predictive of quarterly variations in household consumption, and not of its absolute values; that the index is more predictive in the following trimester, while less predictive synchronously (i.e. in the same quarter); and that its predictive power was stronger between 2009 and 2013 compared to previous years. Furthermore, after 2008, the ICS was also predictive of consumer strategies, particularly those aimed at reducing expenses and focusing on quality (while no relation seems to exist between consumer sentiment and consumers' strategies aimed at discounts and promotions). Implications for marketing and market research are discussed.